FRI0273 EFFECTIVENESS AND RETENTION RATE OF SECUKINUMAB FOR PSORIATIC ARTHRITIS AND AXIAL SPONDYLOARTHRITIS: REAL-LIFE DATA FROM THE ITALIAN LORHEN REGISTRY. (2nd June 2020) - Favalli, E. G.; Marchesoni, A.; Balduzzi, S.; Montecucco, C.; Lomater, C.; Crepaldi, G.; Talamini, S.; Bazzani, C.; Fusaro, E.; Priora, M.; Iannello, A.; Paolazzi, G.; et al.
Abstract : Background: Observational data on the use of secukinumab for the treatment of spondyloarthritides are still lacking. Large population-based registries that allow long-term follow-up have been increasingly used to investigate the performance of biologic drugs in a real life setting. Objectives: The aim of this study is to evaluate the effectiveness and the retention rate of secukinumab in psoriatic arthritis (PsA) and axial spondyloarthritis (axSpA) patients in a real-life setting over a 3-year follow-up period. Methods: Data of all PsA and axSpA patients (diagnosed according to CASPAR and ASAS criteria, respectively) treated with secukinumab were prospectively collected in the Italian multicentric LORHEN registry. Effectiveness was measured as the mean change from baseline of Disease Activity in PSoriatic Arthritis score (DAPSA) in PsA and Ankylosing Spondylitis Disease Activity Score (ASDAS) in axSpA patients. Rates of DAPSA remission and ASDAS inactive disease were also computed. The 3-year retention rate was calculated by the Kaplan-Meier method and compared between PsA and axSpA by a log-rank test. A descriptive analysis of reasons for discontinuation was performed. Results: The study population included 195 PsA (55.4% females, mean age 50.7 [±11.8] years, mean disease duration 10 [±7.8] years, mean baseline DAPSA 23.12 [±12.3]) and 94 axSpA (61.7% males, mean age 49.1 [±12.7] years, mean disease duration 10.4 [±9.4] years, mean baseline ASDAS 3.41 [±1.1]) patients who received secukinumab as first (26.5 and 33%, respectively) or subsequent biologic agent. Compared with baseline, the 3-, 6- and 12-month mean values of both DAPSA (12.6 [±9], 11.2 [±10.5] and 9.3 [±7.5], respectively) and ASDAS (2.23 [±0.9], 2.15 [±0.9], and 1.84 [±0.9], respectively) were significantly decreased (p<0.001 for all the timepoints). The 3-, 6-, and 12-month rates of remission/inactive disease were 15.5, 25.4, and 30.5% in PsA and 18, 23.7, and 28.6% in axSpA group, respectively. One- and 3-year retention rate (figure 1 ) were respectively 79.4% and 66.6% in PsA and 72.3% and 70.1% in axSpA patients, with no significant difference between the two groups (p=0.517). The most frequent reason for withdrawal was inefficacy in both PsA (n=41) and axSpA (n=20), whereas only 8 PsA and 6 axSpA patients discontinued secukinumab because of adverse events. Conclusion: Our data confirmed in a real-life setting the 1-year clinical efficacy and the 3-year survival of secukinumab in both PsA and axSpA. The safety profile of secukinumab was very favorable for both the indications. No significant differences were observed in the performance of secukinumab between ax-SpA and PsA. References: [1]Deodhar A, et al. Arthritis Research & Therapy; 2019. [2]Mease PJ, et al. RMD Open. BMJ Specialist Journals; 2018;4(2):e000723. [3]Baraliakos X, et al. Clin Exp Rheumatol. 2018 Jan;36(1):50–5. Disclosure of Interests: Ennio Giulio Favalli Consultant of: Consultant and/or speaker for BMS, Eli-Lilly, MSD, UCB, Pfizer, Sanofi-Genzyme, Novartis, and Abbvie, Speakers bureau: Consultant and/or speaker for BMS, Eli-Lilly, MSD, UCB, Pfizer, Sanofi-Genzyme, Novartis, and Abbvie, Antonio Marchesoni Speakers bureau: Abbvie, Pfizer, UCB, Novartis, Celgene, Eli Lilly, Silvia Balduzzi: None declared, Carlomaurizio Montecucco: None declared, Claudia Lomater Consultant of: Advisory board for Sanofi, Novartis, Abbvie, Gloria Crepaldi Consultant of: Advisory board for Sanofi and Celgene, Speakers bureau: BMS, MSD, Silvia Talamini: None declared, Chiara Bazzani: None declared, Enrico Fusaro: None declared, Marta Priora: None declared, Aurora Iannello: None declared, Giuseppe Paolazzi: None declared, Roberto Caporali Consultant of: AbbVie; Gilead Sciences, Inc.; Lilly; Merck Sharp & Dohme; Celgene; Bristol-Myers Squibb; Pfizer; UCB, Speakers bureau: Abbvie; Bristol-Myers Squibb; Celgene; Lilly; Gilead Sciences, Inc; MSD; Pfizer; Roche; UCB